'You have to have a level of trust': Consumer‐described health literacy barriers and enablers to engaging with health care professionals. Issue 1 (20th September 2022) - Wood, Helen; Benino, Diana; Brand, Gabrielle; Clifford, Rhonda; Lee, Kenneth; Seubert, Liza
Abstract: Issue Addressed: Health literacy – the degree to which people can access, understand and use health information – is essential for shared decision‐making and improved health outcomes. Health consumers' ability to engage with health care professionals (HCPs) is influenced by their health literacy capabilities. This research sought to understand health literacy‐related barriers and enablers to engage with non‐physician HCPs as experienced by consumers. Methods: A qualitative descriptive approach was undertaken. A semi‐structured interview guide was used, incorporating five health literacy domains described in the Health Literacy Questionnaire that related to consumers' engagement with health professionals. Audio‐ or digitally‐recorded interviews were conducted with Australian health consumers, and transcribed and themed using the Patient‐centred Access to Care framework as a template. Results: Interviewing 30 consumers revealed that HCPs' clinical skills often enabled consumers to seek engagement; however, during active engagement their interpersonal skills became a key enabler. Conversely, a lack of developed interpersonal skills in HCPs was frequently seen as a barrier to consumer engagement. Barriers to engagement were also created when HCPs' information did not match what consumers discovered from other sources. However, consumers self‐reported that they were unable to appraise health information at least some of the time. Conclusion: Barriers and enablers to consumers' engagement with HCPs were identified across each of the five relevant health literacy domains. So What?: HCPs should be aware of the importance of interpersonal skills and clear health information suitable for consumers with lower health literacy. Additionally, time dedicated to educating consumers on information appraisal could act as a further enabler to effective engagement.